Analisis Tanggap Kemiskinan Dalam Distribusi Dana Zakat(Studi Kasus Pada LAZISMU UMS) - Sa'adah, Hindun Niyatus; , Dr. Agung Riyardi, M.Si (2017)
Among the main problems faced by the Indonesian nation is the problem of poverty. Zakat is one of Islamic approach in poverty alleviation and attainment of equality of welfare. This paper is the result of a study which aims to find out the analysis of poverty response in the distribution of zakat funds, by taking Case Study of Amil Zakat, Infak and Shodaqoh Muhammadiyah (LAZISMU) UMS Institute. This research uses qualitative analysis descriptive form of financial statements and reports of zakat fund distribution to the mustahik in LAZISMU UMS so as to know the effect of zakat fund for poverty response. Based on the results of qualitative descriptive analysis that has been done in this research, LAZISMU UMS as a distribution institution of zakat funds in 2016 succeeded in responding to poverty in the distribution of funds that is by meeting the indicators of needs such as clothing, food, shelter, health, education, compensation and capital Training required the mustahik. Keywords: Zakat, Poverty, LAZISMU